A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ha Tinh Province, Vietnam - Pham, Anh Van; Nguyen, Anh Minh Hoang; Le, Minh Duc; Nguyen, Truong Quang; Nguyen, Hung Viet; Hoang, Ngoc Van; Nguyen, van Thi Hong (Zootaxa, 2026)
A new species of the genus Scincella Mittleman, 1950 is described from Vietnam based on morphological differences and molecular divergence. Scincella vuquangensis sp. nov. is distinguished from its congeners by body size; number of primary temporals; the presence of external ear opening and the absence of lobules on anterior margin; head scalation (loreals, supralabials, infralabials, nuchals); number of midbody scale rows; number of smooth scales across the back; number and size of paravertebral; number of ventral scale rows; number of lamellae beneath finger IV and toe IV; length of toe finger; and color pattern. In phylogenetic analyses, the new species is recovered as a sister taxon to S. rufocaudata. The new species is separated from S. rufocaudata by 9.37–9.64% in pairwise genetic distance, based on a fragment of the mitochondrial COI gene.